Characterization of Steroidal Saponins from Dioscorea villosa and D. cayenensis Using Ultrahigh Performance Liquid Chromatography/Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry - Avula, Bharathi; Wang, Yan-Hong; Wang, Mei; Ali, Zulfiqar; Smillie, Troy J.; Zweigenbaum, Jerry; Khan, Ikhlas A. (Planta Medica, 2014)
Yam (Dioscorea spp.) is an important edible tuber plant used for medicinal purposes to promote health and longevity in Chinese tradition. Steroidal saponins were reported to be the major physiologically active constituents in yams. In this current work, the structural characteristics of steroidal saponins in methanolic extracts from dried rhizomes of two Dioscorea species (D. villosa L. and D. cayenensis Lam.) and dietary supplements have been identified and analyzed using UHPLC/QTOF-MS in both negative and positive ion modes. The fragmentation patterns of reference standards were determined and the steroidal saponins in the extracts were identified or tentatively characterized from their retention times and mass spectra. The fragments produced by collision-induced dissociation (CID) revealed the characteristic cleavage of glycosidic bonds, and the fragmentation pattern provided structural information about the sugars. Twenty-one saponins, including four tentatively identified compounds, were detected in the crude extracts of two Dioscorea species. These saponins can be used to distinguish D. villosa from D. cayenensis. For example, asperin and gracillin are found only in D. cayenensis, and dioscoreavilloside A and B and parvifloside are only found in D. villosa. This can be used to determine the presence or absence of D. villosa in commercial products, which may help determine the spiking of plant material, and/or prevent the use of potentially mislabeled or misidentified “Dioscorea” material. The analytical method also provided an alternative, fast method for quality control of Dioscorea species in dietary supplements. Principal component analysis showed that Dioscorea species and commercial products were easily distinguished. From this a partial least squares model was constructed to determine what species are in different products.
Keywords: Dioscorea villosa; Dioscorea cayenensis; Dioscoreaceae; UHPLC-QTOF-MS; steroidal saponins; furostan saponins; spirostan saponins